All for one and FOSL1 for all: FOSL1 at the crossroads of lung and pancreatic cancer driven by mutant KRAS. (4th May 2017) - Vallejo, Adrian; Valencia, Karmele; Vicent, Silvestre
ABSTRACT: KRAS proto-oncogene, GTPase ( KRAS ) remains refractory to current therapies. We devised an integrative cross-tumor approach to expose common core elements up-regulated in mutant KRAS cancers that could provide new treatment opportunities. This approach identified FOSL1 ( Fos-like antigen 1 ) as a clinically and functionally relevant gene in mutant KRAS -driven lung and pancreatic cancers, and unveiled downstream transcriptional targets amenable to pharmacological inhibition